Breast Implant–Associated Anaplastic Large Cell Lymphoma: A Case Report and Review of the Literature. (31st October 2017) - Ezekwudo, Daniel E.; Ifabiyi, Tolulope; Gbadamosi, Bolanle; Haberichter, Kristle; Yu, Zhou; Amin, Mitual; Shaheen, Kenneth; Stender, Michael; Jaiyesimi, Ishmael
Abstract : Breast implant–associated anaplastic large T-cell lymphoma has recently been recognized as an entity, with few reports describing the two common subtypes: in situ (indolent) and infiltrative. Recently, the infiltrative subtypes have been shown to be more aggressive requiring adjuvant chemotherapy. We report a rare case of breast implant–associated anaplastic large cell lymphoma (BIA-ALCL) in a 65-year-old Caucasian female following silicone breast implantation and multiple capsulectomies. We discuss the rare presentation of this disease, histopathologic features of the indolent and infiltrative subtypes of ALCL, and their clinical significance. We also review the literature for up-to-date information on the diagnosis and clinical management. Treatment modalities including targeted therapy are also discussed. Although BIA-ALCL is rare, it should always be considered as part of the differential diagnosis especially in women with breast implants. Given the increasing rate of breast reconstruction and cosmetic surgeries, we anticipate a continuous rise in incidence rates of this rare disease; thus, caution must be taken to avoid misdiagnosis.